Pengembangan Sistem Informasi Pengelolaan Proyek pada CV Tricore Media Teknologi - Fandi Halim; Gunawan Gunawan; Indra Prasetya; Iga Mentari (Fakultas Informatika, 2015)
CV. Tricore Media Technologi is a project-based company which its domain is on information and communication technology. When carrying out its activities, this company is experiencing several problems such as archieve and document management for each project, thus the company become slower on processing data in order to kow the progress of each project being worked on. Further more, the financial administration in the company is also experiencing problems on determining due payment. This study is aiming on developing a web-based project management information system with several important feature embedded. There is also notification feature to help the company on knowing the progress of each project being worked on and to fid information about the due payment.